2016
DOI: 10.3389/fphar.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Anti-Inflammatory Effects of Clinacanthus nutans Lindau Extracts: Inhibition of Cytokine Production and Toll-Like Receptor-4 Activation

Abstract: Clinacanthus nutans has had a long history of use in folk medicine in Malaysia and Southeast Asia; mostly in the relief of inflammatory conditions. In this study, we investigated the effects of different extracts of C. nutans upon lipopolysaccharide (LPS) induced inflammation in order to identify its mechanism of action. Extracts of leaves and stem bark of C. nutans were prepared using polar and non-polar solvents to produce four extracts, namely polar leaf extract (LP), non-polar leaf extract (LN), polar stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 38 publications
(51 reference statements)
3
63
0
1
Order By: Relevance
“…A total 50 μg protein was subjected to sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) followed by immunoblotting as described in previous studies [22, 3233]. Primary monoclonal antibodies that target phosphorylated AKT (p-AKT) S473 and T308, as well as total AKT were obtained from Cell Signaling, USA.…”
Section: Methodsmentioning
confidence: 99%
“…A total 50 μg protein was subjected to sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) followed by immunoblotting as described in previous studies [22, 3233]. Primary monoclonal antibodies that target phosphorylated AKT (p-AKT) S473 and T308, as well as total AKT were obtained from Cell Signaling, USA.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the most used part of the plant was the leaf, and the common prescription method was decocting the plant with water for oral ingestion or soaked it in alcohol for a week for topical application on an affected area . Focusing on the present study's interest, works related to the anti‐inflammatory properties of C. nutans have been performed both in vitro and in vivo . These studies suggested that the anti‐inflammatory activity of C. nutans was mostly exhibited by alcoholic preparation of the C. nutans extract.…”
Section: Introductionmentioning
confidence: 95%
“…8 Focusing on the present study's interest, works related to the anti-inflammatory properties of C. nutans have been performed both in vitro and in vivo. [9][10][11][12][13][14] These studies suggested that the anti-inflammatory activity of C. nutans was mostly exhibited by alcoholic preparation of the C. nutans extract.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to this strain led to increased immunity of intestinal mucosa and regulated the Th17/Treg balance, which was owed to TLR pathway in DCs [88] . Another aspect with regard to immunomodulation is that pretreatment with probiotics may decrease various cytokines and chemokines production and induce anti-inflammatory molecules, mainly through Th17/Treg, TLRs, or NF-κB signaling pathways [89, 90] . Probiotic Lactobacillus rhamnosus GR-1 ameliorated E. coli induced disruption of cellular structure and inflammation, partly by promoting TLR2 and NOD1 synergism and decreasing NLRP3 inflammasome activation [33] .…”
Section: Molecular Mechanisms Of Probiotics In Gi Diseasesmentioning
confidence: 99%